Influence of surfactant to foamed concrete mix / Nurul Aini Mohamed - Mohamed, Nurul Aini (2006)
Lightweight Concrete or Foamed Concrete is developed as a new technology in building construction. It is developed to replace the conventional concrete in order to reduce the density of concrete with a practical range of density 250 - 1800 kg/m3. As conventional concrete the materials used are cement, sand, aggregate and water so does the foamed concrete are also used the same material. However, the coarse aggregate used in the conventional concrete is replaced with the foaming agent. The foaming agent acts as to reduce the weight of concrete. Therefore, foamed concrete is flowable and self-compacting which it may reduce the machinery usage and save in manpower. Two types of foaming agent used in this study are protein based as surfactant and synthetic based. This study is conducted to analyse the effect of surfactant to the compressive strength and indirect tensile strength of foamed concrete and to get the optimum percentage of surfactant when the density and cement-sand ratio are differ for compressive and indirect tensile test. The density of foamed concrete are tested in the range of 1200 kg/m3 - 1400 kg/m3 with the cement-sand ratio 1:1, 1:2 and 1:3. The surfactant added in the foaming agent with increment of 20% from 0% to 60% in each condition. Based on the result obtained from the laboratory testing, the strength for both compressive and indirect tensile test was reduced when the surfactant percentage increased. The strength for both tests increased when no surfactant added in the foaming agent especially for 1:1 cement-sand ratio. This is because the materials were having good bond to each other. In addition, the strength was increased when the density is increased. As a conclusion, it was suggested that the surfactant based should be change to the latest surfactant in market today.